2017
DOI: 10.3390/educsci7020056
|View full text |Cite
|
Sign up to set email alerts
|

‘Chinuch Mashlim’—Losses and Displacements at the Contact Zone between English and Hebrew: Transcending Monolingual Boundaries

Abstract: This conceptual article investigates the losses and displacements taking place at the contact zone between English and Hebrew. The study focuses on one Hebrew term 'chinuch mashlim' [complementary education in Hebrew] and its relationships with its equivalent English term 'informal education'. By applying a theoretic-linguistic analysis process, the study traces the socio-historical-political meanings of 'chinuch mashlim' and relates this theoretical construct to its English counterpart, 'informal education'. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The survivors also highlighted the key role of the education system in promoting education regarding healthy sexuality and sexual abuse. In Israel, the Ministry of Education conducts a compulsory program (called "Life Skills") in elementary and middle schools that deals with sex education and sexual violence, among other topics [86]. However, in line with previous studies, the participants indicated that the sex education they received was brief and inadequate.…”
Section: Discussionmentioning
confidence: 79%
“…The survivors also highlighted the key role of the education system in promoting education regarding healthy sexuality and sexual abuse. In Israel, the Ministry of Education conducts a compulsory program (called "Life Skills") in elementary and middle schools that deals with sex education and sexual violence, among other topics [86]. However, in line with previous studies, the participants indicated that the sex education they received was brief and inadequate.…”
Section: Discussionmentioning
confidence: 79%